Informal caregiver training for people with chronic pain in musculoskeletal services (JOINT SUPPORT): protocol for a feasibility randomised controlled trial. Issue 1 (27th January 2023) - Smith, Toby; Khoury, Reema; Ashford, Polly-Anna; Hanson, Sarah; Welsh, Allie; Clark, Allan B; Dures, Emma; Adams, Jo
Abstract : Introduction: Chronic musculoskeletal (bone, joint or muscle) pain is disabling. People with it frequently have difficulties in managing everyday activities. Individuals may rely on family members or friends to support them. These people are known as informal caregivers. No interventions have previously addressed the health needs of people with chronic musculoskeletal pain and their caregivers. In response, the JOINT SUPPORT programme was developed. In this study, we will assess the feasibility and acceptability of conducting a pragmatic, multicentre, randomised controlled trial (RCT) to test the clinical and cost-effectiveness of the JOINT SUPPORT programme to support these individuals. Methods and analysis: This will be a mixed-methods feasibility RCT. We will recruit 80 patients with chronic musculoskeletal pain with their informal caregivers. Patients will be randomised to usual National Health Service (NHS) care OR usual NHS care plus a caregiver–patient dyad training programme (JOINT SUPPORT). This programme comprises of five, 1-hour, group-based sessions for patients and caregivers, delivered by trained physiotherapists or occupational therapists. It includes developing skills in: understanding pain, pacing, graded activity, fear avoidance and goal-setting, understanding benefits of physical activity and skills in medication management. This will be re-enforced with a workbook. After the group-based sessions, patients and caregivers will be supported through three telephone sessions with a therapist. Data collected at baseline and 3 months will include: screening logs, intervention logs, fidelity checklists and clinical outcomes on quality of life, physical and emotional outcomes, adverse events and resource use. Qualitative research with 24 patient–caregiver dyads and 12 healthcare professionals will explore the acceptability of trial processes. Stop–go criteria will inform the progression to a full trial. Ethics and dissemination: Ethical approval was obtained on 22 February 2022 (National Research Ethics Committee Number: 22/NW/0015). Results will be reported at conferences, peer-review publications and across social media channels. Trial registration number: ISRCTN78169443 .